2011
DOI: 10.1186/1747-597x-6-26
|View full text |Cite
|
Sign up to set email alerts
|

The SCIDOTS Project: Evidence of benefits of an integrated tobacco cessation intervention in tuberculosis care on treatment outcomes

Abstract: BackgroundThere is substantial evidence to support the association between tuberculosis (TB) and tobacco smoking and that the smoking-related immunological abnormalities in TB are reversible within six weeks of cessation. Therefore, connecting TB and tobacco cessation interventions may produce significant benefits and positively impact TB treatment outcomes. However, no study has extensively documented the evidence of benefits of such integration. SCIDOTS Project is a study from the context of a developing nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 22 publications
2
75
0
Order By: Relevance
“…The stigma associated with TB is well documented, and this often leads to changes in conceptions of self and social role (Christodoulou, 2011). This study reinforces the message from previous studies of the effectiveness of targeting TB patients in smoking cessation programs (Awaisu et al, 2011;El-Sony et al, 2007;Ng et al, 2008). McBride et al, 2003) characteristics of teachable moments may also explain why those with a respiratory condition other than TB were not so successful in their cessation.…”
Section: Interpretation and Implications Of Findingssupporting
confidence: 79%
See 1 more Smart Citation
“…The stigma associated with TB is well documented, and this often leads to changes in conceptions of self and social role (Christodoulou, 2011). This study reinforces the message from previous studies of the effectiveness of targeting TB patients in smoking cessation programs (Awaisu et al, 2011;El-Sony et al, 2007;Ng et al, 2008). McBride et al, 2003) characteristics of teachable moments may also explain why those with a respiratory condition other than TB were not so successful in their cessation.…”
Section: Interpretation and Implications Of Findingssupporting
confidence: 79%
“…This offers opportunities for teachable moments to provide cessation to patients suspected of TB who also smoke (Ng et al, 2008). For example, DOTS facilitators can be trained to provide advice and counseling to patients with suspected TB (Awaisu et al, 2011;El-Sony et al, 2007) This paper analyses data from the ASSIST trial Siddiqi et al, 2010) which tested a behavioral support session with (BSS+) and without bupropion (BSS), delivered by DOTS facilitators to provide smoking cessation support to patients with suspected TB. Both treatment conditions led to an eight-to nine-fold increase in continuous smoking abstinence compared to the usual care; more details can be found in the published protocol and findings of this trial Siddiqi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[6,68] There are some data to show that integrating smoking cessation efforts (support plus NRT) with TB treatment is feasible, [69] improves quit rates (77% v. 8.7%, respectively) and completion of TB treatment (97.5% v. 84.8%, respectively). [70] It is unclear, however, whether stopping smoking during TB therapy will reduce the excess mortality associated with smoking and TB, [71] nor are there any efficacy data available on whether using bupropion or varenicline with concomitant anti-TB therapy may be of benefit. Smoking cessation should, however, be encouraged in all TB patients and appropriate support provided.…”
Section: Tuberculosismentioning
confidence: 99%
“…Previous studies have shown that the introduction of tobacco cessation services is feasible and results in smoking quit rates of up to 77%, associated with substantial improvements in quality of life and better TB treatment outcomes. 2 The World Health Organization (WHO) and the International Union Against Tuberculosis and Lung Disease (The Union) thus recommend the promotion of smoking cessation as an integral part of TB patient care. 3 In Bangladesh, TB is a major health problem and tobacco use is also common, with 50% of men and 2% of women reporting current smoking.…”
Section: Settingmentioning
confidence: 99%